Different classes of genomic inserts contribute to human antibody diversity - Lebedin, Mikhail; Foglierini, Mathilde; Khorkova, Svetlana; Vázquez García, Clara; Ratswohl, Christoph; Davydov, Alexey N; Turchaninova, Maria A; Daubenberger, Claudia; Chudakov, Dmitriy M; Lanzavecchia, Antonio; de la Rosa, Kathrin (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Recombination of antibody genes in B cells can involve distant genomic loci and contribute a foreign antigen-binding element to form hybrid antibodies with broad reactivity for Plasmodium falciparum. So far, antibodies containing the extracellular domain of the LAIR1 and LILRB1 receptors represent unique examples of cross-chromosomal antibody diversification. Here, we devise a technique to profile non-VDJ elements from distant genes in antibody transcripts. Independent of the preexposure of donors to malaria parasites, non-VDJ inserts were detected in 80% of individuals at frequencies of 1 in 104 to 105 B cells. We detected insertions in heavy, but not in light chain or T cell receptor transcripts. We classify the insertions into four types depending on the insert origin and destination: 1) mitochondrial and 2) nuclear DNA inserts integrated at VDJ junctions; 3) inserts originating from telomere proximal genes; and 4) fragile sites incorporated between J-to-constant junctions. The latter class of inserts was exclusively found in memory and in in vitro activated B cells, while all other classes were already detected in naïve B cells. More than 10% of inserts preserved the reading frame, including transcripts with signs of antigen-driven affinity maturation. Collectively, our study unravels a mechanism of antibody diversification that is layered on the classical V(D)J and switch recombination.
Keywords: Immunoglobulin Light Chains; Plasmodium falciparum; Mutagenesis, Insertional; Receptors, Antigen, T-Cell; CD antigeny; lehké řetězce imunoglobulinů; Genomics; Leukocyte Immunoglobulin-like Receptor B1; lidé; Receptors, Immunologic; imunoglobulinový receptor leukocytů B1; Antibody Diversity; receptory imunologické; geny pro imunoglobuliny; receptory antigenů T-buněk; inzerční mutageneze; Antigens, CD; rozmanitost protilátek; protilátky protozoální; Antibodies, Protozoan; B-Lymphocytes; B-lymfocyty; Genes, Immunoglobulin; genomika; Humans